2013
DOI: 10.1111/aos.12328
|View full text |Cite
|
Sign up to set email alerts
|

The long term effectiveness and cost‐effectiveness of initiating treatment for ocular hypertension

Abstract: ABSTRACT.Purpose: To investigate the long-term health and economic consequences of direct treatment initiation in ocular hypertension patients. Methods: A cost-effectiveness analysis with a societal perspective and a lifelong horizon was performed. The primary outcomes were the incremental qualityadjusted life years (QALYs) and costs of direct pressure-lowering treatment for ocular hypertension, compared to a strategy where treatment is postponed until conversion to glaucoma has been observed. We used a decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Furthermore, whilst a range of ‘theoretical’ implementation costs were examined in the sensitivity analysis of our model results, it was beyond scope to examine in detail the costs associated with implementing proposed practice; this clearly ought to be the subject of further research along with consideration of the thoughts on increased testing of patients and clinicians [ 23 , 57 ]. Consideration of innovative and affordable health service delivery redesign is likely to be a wider debate that needs to be addressed too, as has been recently suggested for people with ocular hypertension [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, whilst a range of ‘theoretical’ implementation costs were examined in the sensitivity analysis of our model results, it was beyond scope to examine in detail the costs associated with implementing proposed practice; this clearly ought to be the subject of further research along with consideration of the thoughts on increased testing of patients and clinicians [ 23 , 57 ]. Consideration of innovative and affordable health service delivery redesign is likely to be a wider debate that needs to be addressed too, as has been recently suggested for people with ocular hypertension [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…As there is limited capacity in hospital eye-care services, we developed alternative pathways to test whether less-intensive monitoring would be a cost-effective option for a national health service. These alternative monitoring scenarios were developed in consultation with ophthalmologists, nurses, patients and the public8 and a recent economic evaluation in the Netherlands that suggested that a treating OHT irrespective of glaucoma risk was a cost-effective approach in a Dutch context 20. As neither of the extreme scenarios based on NICE were cost-effective compared with minimal glaucoma monitoring, it is unlikely that any other strategy consistent with NICE guidance would be cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…A similar evaluation was conducted in the Netherlands, investigating direct treatment initiation in OHT evaluated from a societal perspective with a lifetime horizon 20. Direct pressure-lowering treatment was less costly and more effective than a strategy of delaying treatment until early signs of glaucoma are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it was argued that analyses based on the cohorts of OHTS represent a relatively low-risk population. With a patient-level simulation model, van Gestel et al 39 suggested that an early treatment strategy is an advantage in a heterogeneous population of OHT patients. In addition, they also suggested that a 'watchful waiting' approach could be appropriate for the subgroup with a low conversion risk (10 % in 5 years), which agreed with the treatment strategy suggested by an expert panels (to treat a patient with >15 % conversion risk in 5 years).…”
Section: Screening and Treatment Of 'Pre-glaucomatous Status' Screenimentioning
confidence: 99%